2022
DOI: 10.1186/s12877-021-02711-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between sleep quality and psychological distress among older Chinese adults: a moderated mediation model

Abstract: Background Previous research has found a link between sleep quality and psychological distress. However, the underlying mechanisms of this connection have still not been well explored. The aim of this study was to examine the roles of activities of daily living (ADL), physical activity, and perceived social support in the link between sleep quality and psychological distress among older adults. Methods Three thousand two hundred fifty valid individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 50 publications
1
24
0
3
Order By: Relevance
“…These findings are consistent with results from a previous study [8]. Perceived social support improves the health status and prolongs the lifespan of a person by modulating the body's internal immune function.…”
Section: Perceived Social Support Rumination and Sleep Quality Are Co...supporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with results from a previous study [8]. Perceived social support improves the health status and prolongs the lifespan of a person by modulating the body's internal immune function.…”
Section: Perceived Social Support Rumination and Sleep Quality Are Co...supporting
confidence: 93%
“…The physical and mental health disorders of older adults are a major public health concern. Previous studies report that various psychological factors such as rumination, perceived social support, and sleep quality are correlated with depression incidence in older adults [7][8][9]. Several studies report that active physical activity effectively mediates the morbidity and mortality of cardiovascular diseases and ameliorates chronic physical diseases [10][11][12], as well as increases life expectancy thus improving mental health [13].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown an association between poor sleep quality and perennial chronic diseases in older adults, such as type 2 diabetes, hypertension, coronary heart disease, and chronic obstructive pulmonary disease ( 20 , 21 ). Sleep quality is also associated with psychological distress, and older adults who have poor sleep quality are more likely to experience various mental health problems ( 22 ). Therefore, we hypothesize that poor sleep quality is related to the prevalence of multimorbidity in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing trend of aging, China will have 264.02 million older adults over the age of 60 by the end of 2020. 1 Despite the fact that China’s rapid economic growth has helped to improve populations’ overall health and average life expectancy. However, one of the most prominent issues today is the health disparity between urban and rural areas.…”
Section: Introductionmentioning
confidence: 99%